The anti‐anaphylactoid effects of Piperine through regulating MAS‐related G protein‐coupled receptor X2 activation. (27th January 2020) - Qiao, Chuchu; Hu, Shiling; Che, Delu; Wang, Jue; Gao, Jiapan; Ma, Ruiping; Jiang, Wenjun; Zhang, Tao; Liu, Rui
Abstract : Mast cells play an important role in inflammatory and allergic diseases. MAS‐related G protein‐coupled receptor X2 (MRGPRX2) is a novel G protein‐coupled receptor in mast cells that mediates drug‐induced anaphylactoid reactions. Piperine has been reported to have anti‐inflammatory and anti‐allergic pharmacological activities. However, whether the pharmacological effects are regulated by MRGPRX2 has not yet been reported. The purpose of this study was to assess the anti‐anaphylactoid effect of Piperine and to explore its potential mechanism. The anti‐anaphylactoid effect of Piperine was assessed by an in vivo mouse hindpaw extravasation model. Mast cell intracellular calcium mobilization was measured by a calcium imaging assay. An enzyme immunoassay was used to evaluate the release of pro‐inflammatory factors from stimulated mast cells. Activated mast cell related signals were assessed by western blot. A cell membrane chromatography assay was used to determine the binding characteristics of Piperine and MRGPRX2. The results showed that Piperine suppressed mast cell intracellular Ca 2+ mobilization, inhibited cytokines and chemokines release, and down‐regulated the phosphorylation level of phospholipase Cγ1, protein kinase C, inositol 1, 4, 5‐triphate receptor, P38, protein kinase B, and ERK. Meanwhile, Piperine can bind to MRGPRX2 as a specific antagonist. Hence, Piperine can be served as a novel therapeutic drug candidate for MRGPRX2‐mediated anaphylactoid reactions.